2022
DOI: 10.1177/00332941221137233
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Interpersonal Adaptation in Chinese Adolescents After COVID-19: The Mediating Roles of Self-Esteem and Psychological Resilience

Abstract: Previous studies have implied that physical activity profoundly influences interpersonal adaptation. However, this effect and its mechanisms have not been directly verified, especially for adolescents. This study examines the association between physical activity and interpersonal adaptation in adolescents through self-esteem and psychological resilience after the coronavirus disease 2019 (COVID-19) pandemic. Participants included 542 Chinese adolescents (aged 13–18 years; 242 boys and 300 girls). Adolescents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“… Xu et al (2021) discovered that exercise increased people’s resilience by satisfying fundamental psychological demands. Similarly, Lin et al (2022) found a positive association between physical activity and self-esteem, psychological resilience, and interpersonal flexibility indicators in Chinese adolescents. A substantial body of empirical research supports the proposition that consistent participation in physical activity is positively associated with psychological resilience.…”
Section: Hypothesis Operationalizationmentioning
confidence: 75%
“… Xu et al (2021) discovered that exercise increased people’s resilience by satisfying fundamental psychological demands. Similarly, Lin et al (2022) found a positive association between physical activity and self-esteem, psychological resilience, and interpersonal flexibility indicators in Chinese adolescents. A substantial body of empirical research supports the proposition that consistent participation in physical activity is positively associated with psychological resilience.…”
Section: Hypothesis Operationalizationmentioning
confidence: 75%
“…The total physical exercise score was computed using the formula: total physical exercise score = exercise intensity × duration time × exercise frequency, resulting in a total score ranging from 0 to 100 points ( 13 , 14 ). Higher scores indicate a higher level of physical exercise ( 15 ).…”
Section: Scales For Questionnairementioning
confidence: 99%
“…Researchers have classi ed college students' adjustment into four dimensions [13], including academic adjustment, personal emotional adjustment, organizational adjustment, and social adjustment. Interpersonal adjustment is an essential component of college students' social adjustment [14], which is the process by which an individual in an interpersonal relationship adjusts their behaviors to cater the behaviors of others [15], and can signi cantly predict depression [16][17][18].…”
Section: Introductionmentioning
confidence: 99%